THE MEDIATING ROLE OF CONSUMER ASPIRATION IN THE INFLUENCE OF COUNTRY OF ORIGIN ON IPHONE REPURCHASE INTENTION - Jonathan Kevin Suhanto; Agung Artha Kusuma (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This study aims to examine the mediating role of consumer aspiration in the influence of country of origin on repurchase intention. A quantitative, associative approach was employed, with a sample of 100 iPhone consumers from Bali Province. The sampling method used was non-probability purposive sampling, with criteria requiring respondents to have previously purchased and used an iPhone at least once, to have graduated from high school or an equivalent level, and to reside in Bali Province. Data were analyzed using PROCESS macro Model 4, processed with IBM SPSS Statistics 26. The results indicate that (1) country of origin has a positive but non-significant direct influence on repurchase intention; (2) country of origin has a positive and significant influence on consumer aspiration; (3) consumer aspiration has a positive and significant influence on repurchase intention; and (4) consumer aspiration fully and significantly mediates the influence of country of origin on repurchase intention